2019
DOI: 10.3389/fphys.2019.00659
|View full text |Cite
|
Sign up to set email alerts
|

Post-cardioversion Improvement in LV Function Defined by 4D Flow Patterns and Energetics in Patients With Atrial Fibrillation

Abstract: Background Atrial fibrillation (AF) is a prevalent cause of cardiovascular morbidity, including thromboembolism and heart failure. Left ventricular dysfunction (LVD) detected in AF patients may be either precursor or consequence of the arrythmia. Successful cardioversion of chronic AF is often followed by a transient period of left atrial (LA) stunning, where depressed mechanical atrial contraction persists despite reinstitution of sinus rhythm. To determine if AF-associated LVD would improve with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Prior 4D flow studies have primarily focused on patients with a history of AF who were in sinus rhythm during imaging, 38,39 or alternatively on using a binary system and categorizing patients into "in AF" or "in sinus" at the time of imaging based on the ECG display at the MRI scanner. 40 These prior studies have demonstrated that patients in AF during imaging exhibited significantly altered LA hemodynamics (increased stasis, decreased velocities) associated with thrombotic risk, compared to patients in sinus rhythm during imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Prior 4D flow studies have primarily focused on patients with a history of AF who were in sinus rhythm during imaging, 38,39 or alternatively on using a binary system and categorizing patients into "in AF" or "in sinus" at the time of imaging based on the ECG display at the MRI scanner. 40 These prior studies have demonstrated that patients in AF during imaging exhibited significantly altered LA hemodynamics (increased stasis, decreased velocities) associated with thrombotic risk, compared to patients in sinus rhythm during imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of component diastolic KE have found that an increase in Direct Flow proportion was accompanied by an increase in DF end diastolic KE and a reduction in that of the residual volume end diastolic KE (77,78), and that the converse relationship held true where there was reduction in DF proportion (72,75,79)…”
Section: Flow Component Diastolic Kinetic Energymentioning
confidence: 99%
“…The Linköping group reported a change in blood flow after electrical cardioversion. 28,42 They recruited 14 patients and performed 4D flow MRI at two time-points: 2-3 hours (Time-1) and 4 weeks (Time-2) following cardioversion. 28 As a novel point of the analysis, they performed non-rigid registration from all time frames to the early-diastolic time frames based on PC-MRA images.…”
Section: Clinical Studies Of 4d Flow Mri After Electrical Cardioversi...mentioning
confidence: 99%